Inclusão de alunos com deficiência na aula de educação física: identificando dificuldades, ações e conteúdos para prover a formação do professor - Fiorini, Maria Luiza Salzani [UNESP]; Manzini, Eduardo José [UNESP] (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2014)
When teachers are faced with students with disabilities in regular schools, their physical education classes do not run smoothly.Thus, this study aimed to identify the difficulties faced by physical education teachers as they include students with disabilities, and suggest actions and content based on these difficulties intending to promote teacher development. Seventeen physical education teachers who worked in schools from 1st to 5th grade participated in the study. They were divided into two groups: morning and afternoon. Three meetings for each group of teachers were conducted. In two of these meetings, information was collected through Focus Groups, and in another meeting, information was presented to the participants. Content analysis of the categorical type was carried out. From this analysis, categories emerged related to difficulties regarding: 1) training, 2) school administration issues, 3) the student 4) diagnosis; 5) family; 6) teaching resources; 7) teaching strategies; 8) Physical Education. Given the results, several proposals were suggested and content to improve the teachers' development. We concluded that when suggesting a program for training teachers of Physical Education focusing on inclusion, one must identify and acknowledge the difficulties that emerge, since the teachers reported that it was not enough to know what to do in order to include or to know what resources to select. There were other issues to consider, such as administrative issues, family issues or aspects related to how the school was structured.

O transcorrer habitual das aulas de Educação Física não parece tranquilo quando o professor defronta-se com alunos com deficiência, principalmente no ensino regular. Nesse sentido, objetivou-se identificar as dificuldades encontradas por professores de Educação Física para incluir alunos com deficiência e sugerir ações e conteúdos a partir dessas dificuldades com a intenção de promover a formação dos professores. Participaram da pesquisa 17 professores de Educação Física que atuavam em escolas, do 1° ao 5° ano, divididos em dois grupos: manhã e tarde. Três encontros para cada grupo de professores foram realizados. Em dois encontros foram coletadas informações por meio de Grupo Focal e, no outro encontro, as informações foram apresentadas aos participantes. Realizou-se uma análise de conteúdo do tipo categorial. Dessa análise emergiram oito categorias de dificuldades atribuídas: 1) à Formação; 2) à questão Administrativo-escolar; 3) ao Aluno; 4) ao Diagnóstico; 5) à Família; 6) ao Recurso Pedagógico; 7) à Estratégia de ensino; 8) à Educação Física. Diante dos resultados foram sugeridas ações e conteúdos para promover a formação dos professores. Conclui-se que, ao propor uma formação para professores de Educação Física, com foco na inclusão educacional, é preciso identificar e assumir as dificuldades encontradas, uma vez que os professores relataram que a dificuldade não era, somente, saber o que fazer para incluir, ou qual recurso selecionar, mas que havia outras questões, como, as administrativas, as familiares e as decorrentes da estrutura escolar.
Inclusion of students with disabilities in physical education classes: identifying difficulties, actions, and contents to provide training of teachers
Keywords: Educação Especial; Educação Física; Dificuldades; Formação de Professor; Special Education; Physical Education; Difficulties; Teacher Development